Functional asymmetry of the lower limbs in young soccer players. - Antosiak-Cyrak, K.; Podciechowska, K.; Jajor, J.; Rostkowska, E. (Trends in Sport Sciences, 2015)
Introduction. The authors attempt to examine whether functional differences between the legs in soccer players are similar in different motor tests, and whether possible weaker laterality in soccer players could be the effect of the higher fitness level of their left legs, or the lower fitness level of their right legs. Aim of Study. The aim of the study was to determine the scope of differences between the results of motor coordination tests performed with the right leg and the left leg by boys playing soccer and non-training controls. Materials and Methods. 52 soccer training boys and 25 non-training controls volunteered to participate in the experiment. Motor coordination tests of the left and the right legs were performed by participants in order to assess static balance, rate of movements, dynamic endurance, and kinesthetic differentiation. Results. The greatest differences between the training and non-training boys were found in dynamic endurance (left leg, p < 0.001; right leg, p < 0.01). Coaches` high assessments of players were based on good results of the balance test of the left leg. The differences between the left and the right legs were smaller in the soccer players than in nontraining boys, particularly when the results of the left legs were better. Conclusions. In both groups under study the functional asymmetry between the right and the left legs in the static balance and dynamic endurance tests exceeded 20%, which may contribute to possible sport injuries. The soccer players` static balance test results indicate the presence of training-induced bilateral transfer of balance ability of the legs.